Ventilation of the Upper Oxygen Minimum Zone in the Coastal Region Off Mexico: Implications of El Niño 2015–2016 - Trucco-Pignata, Pablo N.; Hernández-Ayón, José Martín; Santamaria-del-Angel, Eduardo; Beier, Emilio; Sánchez-Velasco, Laura; Godínez, Victor M.; Norzagaray, Orión (Frontiers in Marine Science, 2019)
As a result of anthropogenic activities, it has been predicted that the ocean will be challenged with rising temperature, increased stratification, ocean acidification, stronger more frequent tropical storms, and oxygen depletion. In the tropical Pacific off central Mexico all these phenomena are already occurring naturally, providing a laboratory from which to explore ocean biogeochemical dynamics that are predicted under future anthropogenic forcing conditions. Here, seasonally anomalous surface tropical waters were detected as a result of the developing "Godzilla El Niño 2015-2016". The incursion of this oxygenated water modified the local structure of an intense and shallow oxygen minimum zone, partially eroding and intensifying the oxycline while having an associated impact on the carbon maximum zone. The core of the oxygen minimum zone (<4.4 μmol kg-1) was centered around 474 m, with a variant upper level between 50 and 360 m depth. Below the dominance of Tropical Surface Waters, the thickness of the oxycline varied between 10 and 325 m, with intensity values up to 11 μmol kg-1 m-1. The change in dissolved inorganic carbon and apparent oxygen utilization yielded a molar ratio of δDIC=0.98×δAOU during June 2015 and of δDIC=1.08×δAOU for March 2016. A further decrease in the average content of dissolved inorganic carbon was observed in the carbon maximum zone for 2016. Traditionally, different explanations have been proposed to account for changing oxygen concentrations in the ocean rather than considering the interactions between multiple forcing factors. Our results highlight the significance of an episodic event like El Niño in the distribution and concentration of O2 and dissolved inorganic carbon and as a plausible mechanism of ventilation and increased oxygen availability in the upper oxygen minimum zone of the tropical Pacific off central Mexico.